MHD Flow of a Jeffrey Fluid with Newtonian Heating. (23rd January 2015) - Farooq, M.; Gull, N.; Alsaedi, A.; Hayat, T.
Abstract : The combined effects of Joule and Newtonian heating in magnetohydrodynamic (MHD) flow of Jeffrey fluid over a stretching cylinder with heat source/sink are addressed. Suitable transformations are considered to reduce the non-linear boundary layer partial differential equations into the ordinary differential equations. Convergent series solutions of the resulting dimensionless problems are obtained. Effects of emerging physical parameters on the velocity and temperature profiles are examined. Comparison between viscous and Jeffrey fluids for different cases of flat plate and cylinder is made. Numerical values of skin friction coefficient and local Nusselt number are tabulated and analyzed for different values of emerging parameters.